Aflatoxin M1 Concentrations, Adulterants, Microbial Loads, and Physicochemical Properties of Raw Milk Collected From Nekemte City, Ethiopia - Leila Nasir; Habtamu Fekadu Gemede (The Scientific World Journal)
Milk is an essential part of the human diet and is a nutrient-rich food that improves nutrition and food security. The aim of this study was to determine the presence and concentration of aflatoxin M1 (AFM1), adulterants, microbial loads, and physicochemical properties of raw cow’s milk (CM) in Nekemte City, Ethiopia. A total of 12 samples of fresh CM were purposefully collected from four kebeles in the city (Bake Jama, Burka Jato, Cheleleki, and Bakanisa Kese) based on the potential of each milk production and distributor site. The AFM1 concentration was determined by high-performance liquid chromatography (HPLC) with a Sigma-Aldrich standard (St. Louis, MO, USA). The concentrations of AFM1 in Bake Jama, Burka Jato, Cheleleki, and Bakanisa Kese were found to be 0.01–0.03 g/L, 0.31–0.35 g/L, 0.19–0.21 g/L, and 0.04–0.07 g/L, respectively. The concentrations of AFM1 in the present study varied significantly (p<0.05) and ranged from 0.01 g/L to 0.35 g/L. These results show that of the 12 samples tested, all were positive for AFM1 and contaminated to varying degrees. The results of this study also revealed that the concentration of AFM1 in 7 (58%) of the 12 milk samples was above the European Union’s (EU) maximum tolerance limit (0.05 g/L). The present study also revealed that of the investigated adulterants, only the addition of water had positive effects on three milk samples, while the remaining adulterants were not detected in any of the milk samples. The total bacterial count (TBC) and total coliform count (TCC) were significantly (p<0.05) different and ranged from 5.53 to 6.82 log10cfumL−1 and from 4.21 to 4.74 log10cfumL−1, respectively. The physicochemical properties of the milk samples in the present study were significantly (p<0.05) different and ranged from 2.8% to 5.75% fat, 7.03% to 9.75% solid-not-fat (SNF), 2.35% to 3.61% protein, 3.33% to 5.15% lactose, 11.54% to 13.69% total solid, 0.16% to 0.18% titratable acid, 26.7 to 32.1°C, 6.35 to 6.55 pH, and 1.027 to 1.030 specific gravity. The physicochemical parameters of the raw milk in the study area met the required quality standards. Hence, further studies are required to determine the extent of the problem and the factors associated with high levels of AFM1 in raw milk in the study areas, including the detection of aflatoxin B1 (AFB1) in animal feed.